Intelligent Computing Technology 8th International Conference, ICIC 2012, Huangshan, China, July 25-29, 2012. Proceedings - Huang, De-Shuang.; Jiang, Changjun; Bevilacqua, Vitoantonio; Figueroa, Juan Carlos; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the first of 3 volumes of refereed conference proceedings of the 8th International Conference on Intelligent Computing, ICIC 2012, held in Huangshan, China, in July 2012. The 242 revised full papers presented were carefully reviewed and selected from 753 submissions. The 84 papers included in this volume are organized in topical sections on evolutionary learning and genetic algorithms, fuzzy theory and models, swarm intelligence and optimization, kernel methods and supporting vector machines, nature inspired computing and optimization, systems biology and computational biology, knowledge discovery and data mining, graph theory and algorithms, machine learning theory and methods, biomedical informatics theory and methods, complex systems theory and methods, pervasive/ubiquitous computing theory and methods, intelligent computing in bioinformatics, intelligent computing in pattern recognition, intelligent computing in image processing, intelligent computing in robotics, intelligent computing in computer vision, intelligent computing in Petri nets/transportation systems, intelligent data fusion and information security, intelligent sensor networks, knowledge representation/reasoning and expert systems, hybrid optimization, and bio-inspired computing and application.
Keywords: Computer science; Artificial intelligence; Computer vision; Optical pattern recognition; Bioinformatics; Computer Science; Artificial Intelligence (incl. Robotics).; Image Processing and Computer Vision; Pattern Recognition; Computational Biology/Bioinformatics.; Information Systems Applications (incl. Internet).; Computation by Abstract Devices